Influence of early specialization in world-ranked swimmers and general patterns to success - Yustres, I.; Santos del Cerro, J.; Martin, R.; González-Mohino, F.; Logan, O.; González-Ravé, J. M. (PLOS ONE, 2019)
Objectives: The primary goal was to examine the influence of early specialization on the performance of senior elite swimmers. Secondly, to provide information about the influence of swim style, distance, sex, status, country, years of high-level competition (YHLC) and age in swimmer`s performance. Design: Data was obtained from International Federation of Swimming (FINA) regarding the participants 2006-2017 of junior and senior World Championships (WCs). The final filtered database included 4076 swimmers after removing those participating only in junior WCs. Method: Cramer V coefficient, double and triple-entry tables were used to measure the relationship between the positions occupied in junior and senior phases. A One-Way ANOVA analysis was used to explain the variables time and rank between swimmers who participated in junior and senior WC or just in senior in all the distances and swim styles (SS). A univariate general linear model (GLM) was used to examine the association between time/rank and category (swimmers that participated previously in junior WC or not); YHLC; country; status (highest finishing position: final/semi-final/heats) and age. Results: Significant differences (p < .001) were found in the GLM, with Rank as dependent variable, for all the variables. Showing that swimmers that participated previously in junior categories obtained greater results in all the interactions, except in 1500m freestyle. Significant differences (p < .001) were found between the variables position and YHLC, showing the variable position improvements as swimmers attended more WCs. Conclusion: Competing in junior WC has a positive influence in achieve posteriori success in FINA WC. YHLC have a positive impact to achieve better positions.